PENERAPAN METODE SIMPLEKS UNTUK MENINGKATKAN KEUNTUNGAN PRODUKSI - Lina, Tirsa Ninia; Marlissa, Belinda Sicilia; Rumetna, Matheus Supriyanto; Lopulalan, Joseph Eliza (STMIK Budi Darma, 2020)
Oma Corry's business is a small-scale bread business in Sorong City, West Papua Province. One of the problems faced by Oma Corry Enterprises is the problem of calculating or determining the maximum profit gained every day from production activities. To calculate the benefits of Bread and Flour Bread and Babengka still use a calculator and write in books so it is less efficient. Whereas now the calculation of maximum profits must be completed quickly and precisely, so we need a system that can provide convenience in calculating profits. To achieve this goal, the simplex method is chosen for the manual calculation process and the POM-QM for Windows tool is used to speed up the calculation process. The result is a maximum profit of IDR 494,000 per day and a more efficient calculation process